Mechanisms involved in the triggering of neutrophil extracellular traps (NETs) by Candida glabrata during planktonic and biofilm growth. Issue 1 (December 2017) - Johnson, Chad; Kernien, John; Hoyer, Amanda; Nett, Jeniel
Abstract Candida spp. adhere to medical devices, such as catheters, forming drug-tolerant biofilms that resist killing by the immune system. Little is known about howC .glabrata, an emerging pathogen, resists attack by phagocytes. Here we show that upon encounter with planktonic (non-biofilm)C .glabrata, human neutrophils initially phagocytose the yeast and subsequently release neutrophil extracellular traps (NETs), complexes of DNA, histones, and proteins capable of inhibiting fungal growth and dissemination. When exposed toC .glabrata biofilms, neutrophils also release NETs, but significantly fewer than in response to planktonic cells. Impaired killing of biofilm parallels the decrease in NET production. Compared to biofilm, neutrophils generate higher levels of reactive oxygen species (ROS) when presented with planktonic organisms, and pharmacologic inhibition of NADPH-oxidase partially impairs NET production. In contrast, inhibition of phagocytosis nearly completely blocks NET release to both biofilm and planktonic organisms. Imaging of the host response toC .glabrata in a rat vascular model of infection supports a role for NET releasein vivo . Taken together, these findings show thatC .glabrata triggers NET release. The diminished NET response toC .glabrata biofilms likely contributes to the resilience of these structured communities to host defenses.